2008
DOI: 10.3174/ajnr.a1350
|View full text |Cite
|
Sign up to set email alerts
|

A Spectrum of Unusual Neuroimaging Findings in Patients with Suspected Sturge-Weber Syndrome

Abstract: BACKGROUND AND PURPOSE: Sturge-Weber syndrome (SWS) is frequently associated with neurologic complications such as seizures, so diagnosing this condition has important implications for patient management. The purpose of this study was to report unusual neuroimaging findings in patients with facial port-wine stain (PWS) and clinically suspected SWS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 25 publications
0
47
0
2
Order By: Relevance
“…Two studies were excluded from analysis; one included only individuals with confirmed leptomeningeal angiomatosis on MRI and the other was a single‐case report . Definitions of high‐risk PWS differed between studies . Dutkiewicz and colleagues and Waelchli and colleagues classified hemifacial, median and forehead PWS phenotypes as high‐risk, whereas Piram and colleagues and Adams and colleagues used old definitions based on involvement of the first division of the trigeminal nerve.…”
Section: Results Of the Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies were excluded from analysis; one included only individuals with confirmed leptomeningeal angiomatosis on MRI and the other was a single‐case report . Definitions of high‐risk PWS differed between studies . Dutkiewicz and colleagues and Waelchli and colleagues classified hemifacial, median and forehead PWS phenotypes as high‐risk, whereas Piram and colleagues and Adams and colleagues used old definitions based on involvement of the first division of the trigeminal nerve.…”
Section: Results Of the Literature Reviewmentioning
confidence: 99%
“…The presence of leptomeningeal angiomatosis was considered a direct feature of SWS (typically involving the posterior parietal or occipital cortex ipsilateral to the PWS), although a spectrum of indirect findings were deemed suggestive (Table ). Dutkiewicz and colleagues and Adams and colleagues defined direct and indirect MRI features of SWS. Subjects were classified as having SWS based on the presence of leptomeningeal angiomatosis on MRI or indirect MRI signs with seizures or other neurodevelopmental disorder .…”
Section: Results Of the Literature Reviewmentioning
confidence: 99%
“…Cet angiome est souvent situé dans la région pariéto-occipitale et est généralement homolatéral à l'angiome cutané, même s'il peut être bilatéral ou controlatéral [10]. Les autres anomalies pouvant être observées sont des calcifications corticales, un élargissement des plexus choroïdes, une absence de drainage veineux superficiel et une atrophie corticale [8,11]. Toutes ces anomalies sont généralement précoces, mais ne sont pas toujours visibles à quelques mois de vie.…”
Section: Imagerie Cérébraleunclassified
“…SWS'de serebellar atrofi sık görülen bulgular arasında bulunmamaktadır. 15 Atrofiye rağmen hastamızın nörolojik muayenesi migren tarzı baş ağrısı dışında tamamen normal bulunmuştur. SWS'de migrenin mekanizması, epilepsi ve vasküler malformasyonlardakine benzer özelliktedir.…”
Section: Resi̇munclassified